2013
DOI: 10.1177/0733464813487587
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Assessment and Evaluation Into Partnership Initiatives

Abstract: Communities nationwide have formed cross-sector partnerships to face the needs of an aging population, particularly for the purpose of improving long-term supportive service systems. Research is limited on how evaluation strategies are incorporated into partnership work, especially in the field of aging. This retrospective qualitative study reviewed administrative and key informant interview data to examine how 15 community partnerships (CPs) within the Community Partnerships for Older Adults (CPFOA) national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Advocating evaluability as a reason to inhibit adaptations has similarities with findings in a previous study (Viswanathan et al, 2004), which demonstrated that researchers must balance methodological rigor with responsiveness to the community. Our result was further underlined by findings showing the importance of monitoring outcomes in praxis and that researchers are often involved as partners in aging community projects due to their expertise in evaluation (Giunta & Lori Thomas, 2015). However, we found no previous studies demonstrating the interplay within and between reasons to adapt or inhibit adaptations and how they actually influence program content and design ( Figure 1), which our study adds to the current knowledge base.…”
Section: Results Discussionsupporting
confidence: 66%
“…Advocating evaluability as a reason to inhibit adaptations has similarities with findings in a previous study (Viswanathan et al, 2004), which demonstrated that researchers must balance methodological rigor with responsiveness to the community. Our result was further underlined by findings showing the importance of monitoring outcomes in praxis and that researchers are often involved as partners in aging community projects due to their expertise in evaluation (Giunta & Lori Thomas, 2015). However, we found no previous studies demonstrating the interplay within and between reasons to adapt or inhibit adaptations and how they actually influence program content and design ( Figure 1), which our study adds to the current knowledge base.…”
Section: Results Discussionsupporting
confidence: 66%
“…City-university partnerships (CUPs) have the potential to advance sustainability transformations (Giunta and Thomas, 2013;Kreuter et al 2000), but the literature does not offer many examples of long-term CUPs that have achieved this goal. The Audacious Partnerships Process was developed based on the research and experience of the CapaCities network, particularly transformative capacity building, and existing literature on partnership development for sustainability.…”
Section: Transformative Sustainability Partnership Developmentmentioning
confidence: 99%
“…Giunta and Thomas (2015) utilized qualitative data from key stakeholder interviews to evaluate how 15 community partnerships worked effectively. Four components/lessons to facilitate effective community partnerships across sectors thematically emerged from the qualitative data analysis.…”
Section: Describing and Evaluating Novel Programs And Therapies For Omentioning
confidence: 99%
“…The initial articles in this issue represent a progression from descriptive to randomized controlled evaluations of programs and therapies; the latter articles adopt various other methodological strategies to explore how programs work and are translated. Giunta and Thomas (2015) utilized qualitative data from key stakeholder interviews to evaluate how 15 community partnerships worked effectively. Four components/lessons to facilitate effective community partnerships across sectors thematically emerged from the qualitative data analysis.…”
mentioning
confidence: 99%